SISTEM INFORMASI MONITORING SISWA SEBAGAI MEDIA PENGAWASAN ORANG TUA BERBASIS WEBSITE - Yoki Firmansyah; Reza Maulana (STMIK KAPUTAMA, 2021)
The more technology develops, the more all aspects of work are developed, one of which is in the field of education, many information systems have been developed in the world of education, one of which is a website-based student monitoring information system. The research was conducted in SMA Koperasi which so far, to monitor students, parents have to come to the location and ask questions directly, with limited hours, namely during school operational hours, of course this makes it difficult for parents to monitor their children, this problem It should be resolved by creating an information-based system, as for the software development method used, namely the prototyping method, with data collection methods, namely observation, interviews and literature study, the main purpose of creating a website-based student monitoring information system is to provide convenience for people parents in seeing the development of their children in school without having to come to school, and can improve the performance of SMA Koperasi in managing student data in order to provide maximum service to students and parents.